Seismic Anisotropy 1996
DOI: 10.1190/1.9781560802693.ch5
|View full text |Cite
|
Sign up to set email alerts
|

5. From Group or Phase Velocities to the General Anisotropic Stiffness Tensor

Abstract: Two numerical inversions were designed to calculate the 21 independent stiffnesses that define, in general, an anisotropic medium from either group-or phasevelocity data. The accuracy, robustness and computational complexity of the two inversion procedures-group velocity to stiffnesses and phase velocity to stiffnesseswere then compared. This group-velocity inversion overcomes the difficulty of calculating group velocity in a prescribed direction and can calculate group velocities accurately even in directions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 9 publications
2
45
0
Order By: Relevance
“…We have modified Vestrum's original phasevelocity inversion code (Vestrum et al, 1996;Vestrum, 1994) parameterization imposes no assumptions on the orientation of the anisotropy of the sample. It also naturally provides a series of best-fitting stiffnessmatrix results of progressively lower anisotropic symmetry, allowing the likely symmetry system of the sample to be determined from the data, instead of needing to be assumed beforehand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have modified Vestrum's original phasevelocity inversion code (Vestrum et al, 1996;Vestrum, 1994) parameterization imposes no assumptions on the orientation of the anisotropy of the sample. It also naturally provides a series of best-fitting stiffnessmatrix results of progressively lower anisotropic symmetry, allowing the likely symmetry system of the sample to be determined from the data, instead of needing to be assumed beforehand.…”
Section: Discussionmentioning
confidence: 99%
“…We have replaced the 21-constant parameterization in Vestrum's phase-velocity inversion code (Vestrum et al, 1996;Vestrum, 1994) with our 12-dimensional parameterization. By using only 12 parameters, we explicitly excluded any result less symmetric than arbitrarily oriented orthorhombically anisotropic media.…”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, the active area of the piezoelectric element is 3 mm in diameter, which is 1/17 of the diameter of the sample, and the natural frequency of the transmitter is 2.5 MHz. Following Vestrum (1994), we conclude that the measured velocities are the ray velocities.…”
Section: Estimation Of Symmetry Axismentioning
confidence: 99%
“…Vestrum (1994); Vestrum et al (1996) demonstrated that by using a large number of high-quality P-and S-wave velocity measurements, he could successfully invert for the complete set of 21 elasticity parameters that best fit the velocity measurements in the least-squares sense. His method makes no prior assumptions about the symmetry or orientation of the rock.…”
Section: Introductionmentioning
confidence: 99%